Tasawuf dan Problematika Modernitas: Menimbang Maqamat dan Ahwal Abu Nashr as-Sarraj - Arrasyid Arrasyid (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Modernity with the sparkling development of science and technology is not bringing people closer to the happiness of life, but instead increasingly becoming anxious because of the luxury of life that he achieved. In this context, Sufism is often believed to be an oasis for the problems of modernity. The purpose of this study is to describe and review the concepts of maqamat and ahwal in Sufism presented by Abu Nashr as-Sarraj and analyze their relevance to modern human problems. This research is a library research, with the data source in the form of library materials such as books, journals and scientific articles. In accordance with the type, the data collection in this study uses library research methods that are analyzed using the method of description and data analysis. The results of this study indicate that in the view of Abu Nashr as-Sarraj, maqamat is divided into seven levels: taubat, wara’, zuhud, fakir, sabar, tawakal, and ridha. As for the ahwal is divided into: muraqabah, mahabbah, khauf, raja’, syauq, ‘uns, tuma’ninah, musyahadah, and yaqin. Maqamat and ahwal in Sufism is a method in Sufism that can be used as an alternative offer and guidelines for modern humans to achieve the ultimate closeness to Allah SWT in order to obtain true happiness.